Creation of sequence-regulating polyhydroxyalkanoate (PHA) synthases with improved thermostability using a full consensus design for the biosynthesis of 2-hydroxyalkanoate-based PHA block copolymers - Furukawa, Shoko; Nakagawa, Naoya; Hachisuka, Shin-ichi; Nakano, Shogo; Tomita, Hiroya; Kikukawa, Hiroshi; Matsumoto, Ken'ichiro (Polymer degradation and stability, 2025)
•Full consensus design algorithm created new block copolymer-producing PHA synthases.•The designed enzymes exhibited broad substrate scope and high thermostability.•P(3HB-co-29 mol% glycolate) was synthesized using the designed enzyme at 35 °C. Engineered polyhydroxyalkanoate (PHA) synthase PhaCAR is a chimeric enzyme composed of PhaCs from Aeromonas caviae and Ralstonia eutropha (formally Cupriavidus necator). The enzyme has a broad substrate scope and unique sequence-regulating capacity: spontaneous synthesis of various block copolymers. This study aimed to acquire new sequence-regulating PHA synthases with a broader substrate scope and improved thermal stability. To meet this goal, artificial PHA synthases were designed using the full consensus design (FCD) algorithm. Based on amino acid sequences of PHA synthases with homology to PhaC from R. eutropha in the database, four artificial PHA synthases, FcPhaC1, FcPhaC2, FcPhaC4, and FcPhaC5, were created and expressed in Escherichia coli together with the monomer-supplying enzyme. Cells were cultivated with the supplementation of monomer precursors in the medium. As a result, these four FcPhaCs synthesized poly(3-hydroxybutyrate) [P(3HB)], although polymer production was slightly lower than that obtained using PhaCAR, indicating that the algorithm successfully designed functional enzymes. FcPhaC1, FcPhaC4, and FcPhaC5 remained active after isothermal treatment at 60 °C for 30 min, whereas PhaCAR and FcPhaC2 were inactivated. Therefore, the artificial PhaCs possessed improved thermal stability compared to PhaCAR. The four FcPhaCs synthesized poly(glycolate-co-3HB) [P(GL-co-3HB)] with a block sequence as well as PhaCAR. FcPhaC4 exhibited the highest GL fraction in P(GL-co-3HB) among the PhaCs tested. FcPhaC4 synthesized P(3HB)-b-P(2-hydroxybutyrate) and P(3HB)-b-polylactate, indicating its broad substrate scope. These results demonstrated the effectiveness of the FCD approach for creating sequence-regulating PHA synthases applicable to a wide range of polymer syntheses.